Design of novel semisynethetic metalloenzyme from thermolysin - Abdul Rahman, Mohd Basyaruddin; Jaafar, Ahmad Haniff; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Abdul Wahab, Habibah (BioMed Central, 2007)
Initial applications of biocatalysis involved the used of naturally occurring enzyme. With new challenges in green chemical reaction, biocatalyst that shed the light is metalloenzyme,which function as enzyme and contain metal that are tightly attached and always isolated with the protein[1]. In recent years, enzyme engineering has proven to be an invaluable tool for elucidating biocatalytic mechanisms as well as producing enzymes for industrial purposes.Approaches developed for in vivo chemical modification and in silico computational methods promise to increase the scope and have already been used successfully to alter existing protein so that they have better stability and functionality [2]. This task might be good to address in designing a new biocatalyst with improved properties.